Review of Islamic Business Ethics in Tiens Syariah Multi Level Marketing Business Practices - Al-Amin; Muthoifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Marketing practices carried out using a network system or among the community are often referred to as Multi-Level Marketing is currently a marketing trend used by various companies, both engaged in the provision of goods and services. This research uses qualitative research in the form of a literature study review. Researchers collected some literature on direct selling practices in marketing. The purpose of this study is to determine the Marketing System used by Tiens Group International Corp., as well as its conformity with the principles of Shari'ah. From the results of the study, it can be concluded that the marketing method carried out at Tiens Group International Corp. is using a Multi-Level Marketing system or method. In addition, the results showed the absence of MAGHRIB elements in the Marketing Plan of Tiens Group International Corp. and has been MUI certified since 2009. The transaction process is standardized and the products sold are halal in shari'ah and have benefits. And it can be concluded that the MLM personal selling strategy at Tiens Group International Corp. consists of 4 major parts, namely: (1) how to work, (2) education, (3) tools, and (4) teamwork. It can be seen that jhiang zhi tea sales in 2021 are very high, but in 2023 it decreases to reach only 50 products sold, then it can be seen that in 2023 spirulina sales are getting higher to reach 400 products sold, but in 2022 spirulina product sales drop to reach only 50 products sold, then vitalin sales are very high in 2023 to reach 100 sales, and it can be concluded that the majority of respondents Distributors strongly agree with the product, about 58% strongly agree, 21% agree, 14% disagree, 5% disagree, and 2% strongly disagree.